Temporal Changes of Pyrite Oxidation Rate in Bolivian Sulphidic Mining Wastes - Móricz, Ferenc; Mádai, Ferenc (International Journal of Engineering and Management Sciences, 2019)
Since the 70’s, when huge sulphidic open pits were developed, the acidic rock drainage (ARD) become the leader problem of the sulphidic mining industry. Although the recycling is an essential technology, it cannot cover the demand alone, thus mining activity needs to continue. Acidity in mine drainage commonly requires most of the attention, but the main problem is the caused elevated level of metal mobility and leaching, which are generated by the increased rates of sulphide weathering under acidic conditions. The Itos mine is a polymetallic vein deposit in Bolivia, had been mined for silver and tin until 1990, leaving behind much and huge tailings and mine waste heaps, where quite often the pyrite content exceeds 10 %. Serious ARD effects take place in the mine waste heaps. These processes can be well characterized with the pH 1 or 2 of the seepage water, which forms serious alteration in the waste itself and the neighbouring rocks. In three consecutive years, the pyrite oxidation rate was investigated on the same 7 samples by humidity cell test. 5-6 months pauses were left between the humidity cell test periods, which mimics the alternation of wet and dry periods, typical for the place. The results give much more information, than the oxidation rate in the individual test periods, showing the changes by time. This applied method gave good result to characterize the behaviour of the waste in long-term. The column test was complemented with mineralogical analyses, such as electron probe micro analysis. The mineralogical and column test analyses show, that the changes of the pyrite oxidation rate split the samples into three different groups, one where the oxidation rate decreases, second where it increases with time and the third where oxidation rate is maximal and stays stable for several years.